Colto, competente o consapevole? Modelli di insegnante a confronto - Giuliano Franceschini (Studi sulla Formazione, 2019)
How many and what are the teacher's skills? In the article we try to go to the root of the question, assuming the existence of three models of teacher. The cultural teacher, the competent teacher, the conscious teacher; they represent respectively the primacy of the cultural canon, of technical rationality, of critical reflexivity. They have a long history behind them but coexist in the contemporary teacher. In this way the research on the teacher's competences is articulated in space and time, in the hope of reconstructing the unity of the teaching function.